2020
DOI: 10.3390/cells9122656
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in Several Cutaneous Autoimmune Diseases: Psoriasis, Cutaneous Lupus Erythematosus and Atopic Dermatitis

Abstract: MicroRNAs (miRNAs) are endogenous small non-coding RNA molecules that regulate the gene expression at a post-transcriptional level and participate in maintaining the correct cell homeostasis and functioning. Different specific profiles have been identified in lesional skin from autoimmune cutaneous diseases, and their deregulation cause aberrant control of biological pathways, contributing to pathogenic conditions. Detailed knowledge of microRNA-affected pathways is of crucial importance for understating their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 131 publications
1
24
0
2
Order By: Relevance
“…The hallmark of non-healed wounds is chronic inflammation caused by infiltration of pro-inflammatory immune cells [7]. Therefore, designing strategies based on the regulation of immune cells' functions is a promising approach in regenerative medicine to treat chronic wounds, including diabetic, vascular and pressure ulcers [138].…”
Section: Modulation Of the Immune System To Improve Wound Healingmentioning
confidence: 99%
“…The hallmark of non-healed wounds is chronic inflammation caused by infiltration of pro-inflammatory immune cells [7]. Therefore, designing strategies based on the regulation of immune cells' functions is a promising approach in regenerative medicine to treat chronic wounds, including diabetic, vascular and pressure ulcers [138].…”
Section: Modulation Of the Immune System To Improve Wound Healingmentioning
confidence: 99%
“…A search for miRNAs that are dysregulated in patients with psoriasis revealed that some miRNAs were upregulated in skin biopsies from psoriatic patients (Domingo et al, 2020). Thus, we tested whether the corresponding mouse miRNA isoforms were capable of provoking a scratching behavior in naive animals following subcutaneous injection in the nape of the neck.…”
Section: Trpv4 Genetic Deletion Protects From Mirna-203b-3p-induced S...mentioning
confidence: 99%
“…There are two approaches for employing miRNA as a gene modulator: miRNA inhibitors/antagomirs, and miRNA mimics/agomirs. The miRNA inhibitor/antagomir approach is utilized for the aberrantly expressed miRNAs that are upregulated in diseases, while anti-miRNA or miRNA inhibitors specifically bind to endogenous mature miRNA, thus preventing targeted miRNA expression [ 27 ]. In contrast, miRNAs that are reduced in diseases can be supplied transiently using miRNA mimics and agomirs.…”
Section: Introductionmentioning
confidence: 99%